1998
DOI: 10.1099/0022-1317-79-8-1859
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus population dynamics in human lymphocytes and hepatocytes infected in vitro.

Abstract: We previously found two cell lines (MT-2 and PH5CH) that were susceptible to hepatitis C virus (HCV) infection. Analysis of the infectivity of sera from HCV-positive blood donors for MT-2 and PH5CH cells suggested the cell tropism of HCV. To investigate further the cell tropism of HCV, the dynamics of HCV populations during culture were examined using three MT-2 clones and three PH5CH clones, infected with inoculum 1B-2. To type HCV populations in these infected cells, the HCV hypervariable region 1 (HVR1) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…As an in vitro infection experiment system of HCV, there have been some reports using a human nonneoplastic hepatocyte cell line, PH5CH cells. 10,11,[13][14][15] HCV reportedly multiplied in PH5CH8 cells that were infected with plasma from HCV-infected patients and was released into culture medium. HCV RNA from infected PH5CH8 cells was also confirmed to be replicatable in Huh-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…As an in vitro infection experiment system of HCV, there have been some reports using a human nonneoplastic hepatocyte cell line, PH5CH cells. 10,11,[13][14][15] HCV reportedly multiplied in PH5CH8 cells that were infected with plasma from HCV-infected patients and was released into culture medium. HCV RNA from infected PH5CH8 cells was also confirmed to be replicatable in Huh-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid sequence of core(M) was identical to the consensus sequences from the original inoculum 1B-2 and was the same as the consensus sequence of the HCV 1b genotype (19). Although only 1 aa [aa 70, Arg for core(M) and Gln for core(P)] differed between core(M) and core(P) (19), the amino acid sequence of core(M) differed at 2 and 8 aa from HCV-J (18) and HCV-K (6) strains, respectively. The plasmid vectors expressing E1 and E2 [pCXbsr/E1(P) and pCXbsr/E2(P)] were also constructed from a cDNA (no.…”
mentioning
confidence: 91%
“…A study of the dynamics of HCV populations during culture using three PH5CH clones (PH5CH1, PH5CH7, and PH5CH8) and three MT-2 clones (MT-2A, MT-2B, and MT-2C) found that the amino acid sequences of HCV proteins obtained from the infected cells were identical or very close to the consensus sequences of the proteins derived from the original inoculum used for HCV infection (19). To investigate whether HCV proteins affect certain signal transduction pathways, we made several expression vectors using HCV cDNA clones obtained from HCV-infected cells.…”
mentioning
confidence: 99%
“…[79][80][81] While some of these data should be viewed cautiously, as a variety of techniques were utilized and a limited number of samples [82][83][84] Interestingly, sequence analysis has subsequently revealed that certain viral variants may be selected for growth in extrahepatic cell types, implying that HCV diversity directly impacts cell tropism. 85,86 Furthermore, several studies have described a non-random distribution of HCV sequences in hepatic and extrahepatic compartments, 72,[87][88][89][90][91][92][93][94][95][96] leading to the conclusion that the presence of tissue-specific sequences is compatible with independent viral replication in extrahepatic sites. It has also been speculated that HCV variants within distinct compartments may differ in their sensitivity to interferon, although this hypothesis has not been formally tested.…”
Section: Evidence For Extrahepatic Replication Of Hcvmentioning
confidence: 99%
“…Moreover, it has long been hypothesized that chronic antigen stimulation by HCV activates B cells and may ultimately result in cryoglobulinemia and non-Hodgkin lymphoma. 5 Furthermore, specific genomic regions, such as the 5ЈUTR and HVR-1, have also been identified that may impact cell tropism, 85,86 thereby influencing the extent of extrahepatic replication. There is also evidence to suggest that the HCV core protein can regulate various cellular oncogenes and viral promoters that regulate transformation and/or carcinogenesis.…”
Section: Clinical Implications Of Extrahepatic Replicationmentioning
confidence: 99%